Competências individuais e coletivas percebidas como necessárias para formação de uma equipe com características ambidestras, sob a ótica do gestor e integrantes da equipe - Freitas, Kellen Silva (2021)
In a mature and traditional organization, organizational ambidexterity has allowed its survival in dynamic and competitive environments. There has even been a movement to form teams aimed at meeting the innovation strategies outlined by the organization, and the agents responsible for contributing to this process are the individuals themselves with their individual and collective competences. In this context, the research problem arises: which individual and collective competences are perceived by the manager and team members as necessary for the formation of a team in the RH 4.0 Project with ambidextrous characteristics? To answer this research question, the research objective was to analyze, from the perspective of the manager and team members, the individual and collective competences perceived as necessary for the formation of a team in the RH 4.0 Project, with ambidextrous characteristics, in a company wholesaler in the Triângulo Mineiro region. The theoretical-empirical basis of the research considered studies on dynamic capabilities, ambidexterity, individual and collective competences in teamwork. The approach of this research is qualitative, of the descriptive type, and the data collection techniques used were: (i) interview with a semi-structured script with the manager of the RH 4.0 Project; (ii) documentary research on the project; (iii) application of an electronic form in Google Forms to the manager and team members, allowing triangulation of data sources and forms of collection. The research results showed that the individual competences proposed by Costa et al. (2020) most valued by the manager were, in this order: Leadership, Interpersonal Relationships and Teamwork, while for team members they were: Teamwork, Interpersonal Relationships, Negotiation, Leadership and Flexibility. The collective competences perceived as necessary by the manager were: interaction and cooperation, and those perceived by the team members were: Mutual Trust, Communication, Sharing and Continuous Learning. Structural ambidexterity was not verified in the RH 4.0 project, however its existence was noted due to the contradictory need of the project between maintaining the processes and automating them, while contextual ambidexterity focused on the individual. The ambidextrous behaviors perceived as necessary by the manager for the project were: ability to always be motivated and informed and to act spontaneously and autonomously; multitasking and cooperation; and for team members, they were: ability to encourage adaptation actions to new opportunities, in line with the overall business strategy; ability to always be motivated and informed and to act spontaneously and autonomously; and ability to act outside the confines of their work and take actions in the interests of the organization. As a technological product, this research gave rise to the creation of an instrument for the organization to identify individual and collective competences in a structure with ambidextrous characteristics, including interview questions and the electronic form, with recommendations for application and analysis.